Ilizarov technique in an adolescent patient with progressive pseudorheumatoid dysplasia: A case report. Issue 31 (August 2018) - Xiao, Ke; Li, Tao; Jiang, Yaping; Li, Zheng; Zhu, Qiankun; Wu, Zhihong; Weng, Xisheng
Abstract: Rationale: Progressive pseudorheumatoid dysplasia (PPD) is a rare autosomal recessive inherited disease that causes severe systemic joint deformity and articular dysfunction in young patients. Patient concerns: Ilizarov technique treatment in PPD patients has never been reported before. Diagnoses: A 17-year-old male patient presented with a 10-year history of polyarthritis and 4-year history of progressive hip and knee pain and stiffness. Genetic testing for the WISP3 gene was done and showed compound heterozygous mutations: NM_198239.1 (WISP3):c.1064_1065dupGT (p.Gln356ValfsTer33) and NM_198239.1 (WISP3):c.643+2T > C. Interventions: Taking his young age into consideration, the Ilizarov external fixation technique was adopted for the treatment of the deformity in knees. Outcomes: One year after the operation, the improvement of joint deformity was satisfactory. Lessons: The Ilizarov technique is economical and less invasive, and most importantly, it can delay the possible arthroplasty. It gives young PPD patients with arthropathy an alternative treatment.